Some Philological Notes on the Mäṣǝḥafä ‘Ǝräfǝtä läMaryam “Liber Requiei” (LR) - Abraha, Tedros (Apocrypha, 2012)
Abstract The article deals with the Gǝ’ǝz version of the Liber Requiei (The Book of [ Mary’s ] Rest), the Mäṣǝḥafä ‘Ǝräfǝtä läMaryam. There is little doubt that the Gǝ’ǝz translation was performed on a lost Greek text, an aspect which together with the paucity of witnesses of the Gǝ’ǝz makes this work a privileged research item. The Gǝ’ǝz version of the Liber Requiei is an indispensable avenue for the reconstruction of the lost Greek original, a term of comparison for the Syriac versions that descended from it and an important example of archaic translation practice from Greek into Gǝ’ǝz. The linguistic quality of the Gǝ’ǝz text is so harsh that the work is virtually unknown to the vast majority of Ethiopian church men and scholars. The pioneering edition and Latin version of Victor Arras (upon which two Italian translations were produced) has the merit of unearthing a text which otherwise would have probably fallen into oblivion. A re-edition of the manuscripts with a fresh faithful translation of the Mäṣǝḥafä ‘Ǝräfǝtä läMaryam would be very useful. Abstract L’article traite de la version Gǝ’ǝz du Requiei Liber (Le Livre du Repos de Marie), le Mäṣǝḥafä ‘Ǝräfǝtä läMaryam. Nul doute que la traduction Gǝ’ǝz a été réalisée sur un texte grec perdu, un aspect qui, avec la rareté des témoins Gǝ’ǝz, fait de ce travail un thème de recherche privilégié. La version Gǝ’ǝz du Liber Requiei est indispensable pour la reconstruction de l’original grec perdu et pour une comparaison avec les versions syriaques qui en dérivent. En outre, elle illustre remarquablement la pratique archaïque de la traduction du grec en Gǝ’ǝz. La qualité linguistique du texte Gǝ’ǝz est si impénétrable que le travail est pratiquement inconnu par la grande majorité des hommes d’église et des chercheurs éthiopiens. L’édition (et la version latine de Victor Arras), sur laquelle deux traductions italiennes ont été produites, a le mérite pionnier de déterrer un texte qui, autrement, serait probablement tombé dans l’oubli. Une réédition des manuscrits avec une nouvelle traduction fi dèle au Mäṣǝḥafä ‘Ǝräfǝtä läMaryam serait très utile.